BEA MATRAI DI INDONESIA - T. Rahmah Rindiyani; Ayla Rizki Janira; Ardiansyah Dalimunthe; Rafly Ramadhan Simanjuntak; Dini Vientiany (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study examines stamp duty in Indonesia as a form of taxation imposed on documents with legal and economic value. The purpose of this research is to analyze the function of stamp duty, the types of documents subject to and exempt from it, as well as its impact on the validity and evidentiary strength of documents, including electronic documents (e-stamps). This research uses a qualitative method with a library research approach, utilizing legal regulations, books, and academic journals as sources. The results show that stamp duty does not determine the legal validity of an agreement but serves as an administrative requirement that strengthens the evidentiary value of documents in court. Furthermore, technological developments have led to the emergence of e-stamps, which have equal legal function and status as conventional stamps. However, challenges remain in their implementation, including limited public understanding and regulatory gaps in adapting to technological advancements. Therefore, regulatory adjustments and increased public awareness are necessary to ensure legal certainty and effectiveness in the application of stamp duty in Indonesia. Keywords: Stamp duty, legal documents, evidentiary strength, e-stamp, legal certainty